Utopias and realities of urban sustainable development : new alliances between economy, environment and democracy for small and medium-sized cities : conference proceedings,Turin-Barolo, 19-21 September 1996 - Mega, Voula P; Petrella, Riccardo; Mega, Voula; Bianchi, Ruben (European Foundation for the Improvement of Living and Working Conditions, 1997)
Is the "sustainable city" a more credible proposition when it is applied to small and medium sized cities? In 1993, the Foundation initiated a project on medium-sized cities and socio-economic and environment developments in EU regions. The objective being to explore the potential of medium-sized cities and the opportunities they provide for urban and regional development in the new European context. At the Piedmont conference the final case studies, and the draft synthesis reports were presented and discussed. Running through the conference were the common themes of sustainable urban development, respect for natural resources, promotion of local democracy and the fostering of social justice. This publication includes many of the papers presented and discussed at Piedmont.